Debasement of District Councils in Kerala (Economic and Political Weekly December 7, 1991, 1991)
Short of abolishing the district councils altogether, the various amendments made to the District Administration Act of Kerala by the present Congress(I)-led government do everything to negate them, to make them functionless, powerless and completely dependent on the state government for finance.